2013
DOI: 10.1021/ja403471d
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nanostructures with Sizes down to 1 nm: A Macromolecule Analogue

Abstract: Ultrathin nanostructures exhibit many interesting properties which are absent or less-pronounced in traditional nanomaterials of larger sizes. In this work, we report the synthesis of ultrathin nanowires and nanoribbons of rare earth hydroxides and demonstrate some new phenomena caused by their atomic-level lateral size (1 nm), including ligand-induced gelation, self-assembly framework, and conformational diversity. These features are typically, although not exclusively, found in polymer solutions. The propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 113 publications
(157 citation statements)
references
References 48 publications
2
155
0
Order By: Relevance
“…However when the sizes of nanowires narrow down to ultrathin, it would be hard to determine what is defect. Ultrathin nanowires could be flexible, and resemble the viscosity behavior of polymers 170. What is more, ultrathin inorganic nanocoils may mimic the self‐folding behavior of biomacromolecues ( Figure 10 h,i) 171.…”
Section: Novel Structures and Atypical Edgesmentioning
confidence: 99%
See 1 more Smart Citation
“…However when the sizes of nanowires narrow down to ultrathin, it would be hard to determine what is defect. Ultrathin nanowires could be flexible, and resemble the viscosity behavior of polymers 170. What is more, ultrathin inorganic nanocoils may mimic the self‐folding behavior of biomacromolecues ( Figure 10 h,i) 171.…”
Section: Novel Structures and Atypical Edgesmentioning
confidence: 99%
“…Schematic of 2D cluster‐assembly and possible variations in the ultrathin nanoribbon conformation. Reproduced with permission 170. Copyright 2013, American Chemical Society.…”
Section: Novel Structures and Atypical Edgesmentioning
confidence: 99%
“…[ 21 ] Recently, our group have succeeded in synthesizing ultrathin GdOOH nanowires with a width of sub-1 nm and a length of over 500 nm. [ 5 ] The as-synthesized ultrathin nanowire dispersions also exhibit interesting viscous property. Unlike other materials, ultrathin nanomaterials possess a sub-1 nm scale, which means the proportion of surface atoms is much higher than ordinary nanomaterials.…”
Section: Highly Flexible Sub-1 Nm Tungsten Oxide Nanobelts As Effi CImentioning
confidence: 99%
“…Particularly, it was found that 1-D nanostructures with their feature sizes confi ned within 1nm might show great fl exibility in self assembly behavior [ 4 ] and diverse structural conformations [ 5 ] and thus can be regarded as macromolecule analogues like DNA and polymer. These features that soft matter possesses may mean that ultrathin nanostructures might make a great contribution to the blossom of soft matter research.…”
mentioning
confidence: 99%
“…Under the designated reaction conditions, the M n+ ions of (RCOO) n M could be reduced to metal nanocrystals by ethanol, or dehydrate to oxides and/or composite oxides, or react with other anion species from the solution phase to yield a large variety of functional nanocrystals. [32][33][34][35][36][37][38][39] The as-obtained product can be easily collected because of a spontaneous phase-separation process based on the weight of nanocrystals and/or incompatibility between their hydrophobic surfaces and hydrophilic surroundings. This strategy has been demonstrated to be effective in the synthesis of HAp nanocrystals with controllable sizes and shapes comparable with those of other colloidal nanocrystals.…”
Section: Lss Phase Transfer and Separation Strategymentioning
confidence: 99%